Ancient Art from New York Private Collections. Catalogue of an Exhibition held at the Metropolitan Museum of Art, December 17, 1959 – February 28, 1960 - von Bothmer, Dietrich (1961)
pp. 6-11: Ancient Near East (Mesopotamian, Iranian, Luristan).